Novel Insight Into the Role of Immune Dysregulation in Amyotrophic Lateral Sclerosis Based on Bioinformatic Analysis - Xie, Yongzhi; Luo, Ximei; He, Haiqing; Tang, Min (Frontiers in Neuroscience, 2021)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder characterized by the progressive degeneration of motor neurons. Causative pathogenic mechanisms in ALS remains unclear, limiting the development of treatment strategies. Neuroinflammation and immune dysregulation were involved in the disease onset and progression of several neurodegenerative disorders, including ALS. It is important to explore roles of immune cells and genes alterations in ALS. Here, we obtained gene expression profile from Gene Expression Omnibus (GEO) database and conducted bioinformatic analysis. Single-sample gene set enrichment analysis revealed the immune cell infiltration level in most immune cells, such as macrophages, Th1, Th17, activated CD4+ T cells and activated CD8+ T cells, were higher in ALS patients than control. Weight gene correlation network analysis identified immune genes associated with ALS. Pathway analysis showed that these genes were enriched not only in immune-related pathway such as cytokine–cytokine receptor interaction but also in PI3K-Akt and MAPK-ERK signaling pathways. Nineteen immune-related genes (C3AR1, CCR1, CCR5, CD86, CYBB, FCGR2B, FCGR3A, HCK, ITGB2, PTPRC, TLR1, TLR2, TLR7, TLR8, TYROBP, VCAM1, CD14, CTSS and FCER1G) were identified as hub genes based on LASSO analysis. This gene signature could efficiently differentiate ALS patients and non-neurological controls (p<0.001) and accurately predict the occurrence of ALS (AUC=0.829 in primary set; AUC=0.862 in test set). In conclusion, our study provides novel insight into the role of immune-related cells and genes in the pathogenesis of ALS and potential biomarkers for diagnosis and targeted therapy.